Inventarisasi Jenis-Jenis Hama Utama Dan Ketahanan Biologi Pada Beberapa Varietas Kedelai (Glycine maxL. Merril) Di Kebun Percobaan Manggoapi Manokwari - Maria Lowisa Ampnir; Johannes Tethool; Jopie Wempi Pattiasina (Fakultas Pertanian Universitas Papua, 2012)
This objective of the study is to identify the type of insect pestof 10 soybean varieties. The study used descriptive method with field observation technique, whichthen continued by deviation standard measurement. The data were analysed in tabulation, while the insects pest were identified by using insect manual book. The variable of observation were insect pest type, the forms of damaged, the weight of full and empty pod, the number of trunk, fresh weight, dry weight and plant height. The result shows that there are 8 types of main insect pest of soybean such as Ophiomya phaseoli, Lamprosema indicate, Chryzodeixis calcites, Phaedonia inclusa, Spodoptera litura, Nezara viridula, Riptortus linearis and Phiezodorus hybneri. Ophiomya phaseoli is the most insects found in the soybean plants for about 151, following by Riptortus linearis for about 52 and Phiezodorus hybneri for about 32. Among the 10 soybean varieties, Grobogan, Wilis and Kaba were found to be resistant to the pod borer insects pest while varieties resisted to the stem borerinsect pest were Grobodan, Prafi and Kaba. The highest productivity resulted from Cikuray and Anjasmoron which still attacked by the insects.